Effects of demographic and clinical character on differences in self‐care behavior levels with arteriovenous fistula by hemodialysis patients: An ordinal logistic regression approach. Issue 5 (24th January 2022) - Sousa, Clemente Neves; Teles, Paulo; Paquete, Ana Rita Cabral; Dias, Vanessa Filipa Ferreira; Manzini, Carlene Souza Silva; Nicole, Andressa Garcia; Sousa, Rui André Saldanha Santos; de Souza, Lara Helk; Ribeiro, Olga Maria Pimenta Lopes; Lira, Marta Nunes; de Queiroz Frazão, Cecília Maria Farias; Ramos, Vânia Pinheiro; et al.
Abstract: Introduction: Hemodialysis (HD) patients should be trained to develop self‐care behaviors in order to prevent and preserve their arteriovenous fistula (AVF). The aim of this study was identifying the factors that affect the levels of self‐care behavior with AVF by HD patients. Methods: A cross‐sectional study was conducted involving 89 patients. Results: Self‐care levels were negatively affected by patients' location (Azores) and positively affected by marital status, education, employment, AVF duration, and absence of complications with the AVF. Concerning the management of signs and symptoms, self‐care levels were negatively affected by patients' location. Regarding prevention of complications, self‐care levels were negatively affected by age and marital status and positively affected by marital status, employment, chronic kidney disease etiology, AVF duration, and previous AVF. Conclusion: Further studies are required in order to confirm whether the considered factors affect levels of self‐care behaviors with AVF, or whether other factors are needed as well.